2020
DOI: 10.1080/2162402x.2020.1832347
|View full text |Cite
|
Sign up to set email alerts
|

Immune infiltration and immune gene signature predict the response to fluoropyrimidine-based chemotherapy in colorectal cancer patients

Abstract: Fluoropyrimidine-based chemotherapy is an essential component of systemic chemotherapy for colorectal cancer (CRC). The immune response is implicated in chemotherapy-induced cytotoxicity. Here, we reported an immune risk (Imm-R) model for prognostic prediction in patients receiving fluoropyrimidinebased chemotherapy. Gene expression profiles and corresponding clinical information were collected from four data sets and divided into training set (n = 183) and validation set (validation set1: n = 34; validation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…Increased predicted sensitivity was concentrated in the CMS1, the MSI immune subtype. Our observation that inflammation-related gene sets are enriched in CMS1 tumors from obese patients is consistent with the finding that immune infiltration predicts fluoropyrimidine, a DNA replication-based chemotherapy (85). Our findings of differential CMS-dependent differences in predicted drug sensitivity are consistent with the observations that differential response to irinotecan-based compared to oxaliplatin-based chemotherapy (86) and chemotherapy plus bevacizumab compared cetuximab (7, 87) in metastatic CRC clinical trials are CMS-dependent.…”
Section: Discussionsupporting
confidence: 90%
“…Increased predicted sensitivity was concentrated in the CMS1, the MSI immune subtype. Our observation that inflammation-related gene sets are enriched in CMS1 tumors from obese patients is consistent with the finding that immune infiltration predicts fluoropyrimidine, a DNA replication-based chemotherapy (85). Our findings of differential CMS-dependent differences in predicted drug sensitivity are consistent with the observations that differential response to irinotecan-based compared to oxaliplatin-based chemotherapy (86) and chemotherapy plus bevacizumab compared cetuximab (7, 87) in metastatic CRC clinical trials are CMS-dependent.…”
Section: Discussionsupporting
confidence: 90%
“…As Figure 4A indicated, PHF19 was correlated with the immune and stromal scores in KIRC, PRAD and THCA (all data P-values < 0.001). Since immune checkpoint-associated genes participate in the immunosuppressive mechanism that allows tumor cells to escape anti-tumor immunity ( 40 ), we next investigated the correlations between PHF19 expression and immune checkpoint-related genes, including BTLA, CD27, CD274, CD276, CD28, CD40, CD70, CD80, CD86, CTLA4, HAVCR2, HHLA2, ICOS, ICOSLG, IDO1, IDO2, LAG3, PDCD1, TIGIT, TNFRSF9, and TNFSF9 across human cancers from the TCGA cohorts, as shown in Figure 4B . Our results suggested that PHF19 expression was closely associated with almost all immune checkpoint-associated genes in BLCA, BRCA, HNSC, LIHC, PRAD and THCA, implying that PHF19 might conduce to immune escape in these tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Current research evidence suggests a significant influence of KRAS mutation in tumor immunity. An unsupervised hierarchical clustering analysis of immune genes/signatures named the Co-ordinate Immune Response Cluster (CIRC), comprising 28 genes, revealed a relatively high proportion of patients with KRAS mutation in the cluster associated with low inhibitory molecule expression [ 13 , 14 ]. In addition, immunophenotyping of colon tumors from mice indicated an association between Kras mutation and an immunosuppressive microenvironment characterized by decreased T-cell infiltration and increased infiltration of myeloid-derived suppressor cells (MDSCs) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%